An Expedient, Direct, Three-Component Approach for the Synthesis of 4-Thioarylpyrroles - Rajeshkumar, Venkatachalam; Neelamegam, Chinnaraj; Anandan, Sambandam (Synthesis, 2019)
A three-component strategy for the synthesis of 4-thioarylpyrroles from 1,4-enediones, thiols, and ammonium formate in one-pot has been developed. The reaction proceeds through the sequential thiol-Michael/Paal–Knorr reaction of 1,4-enediones with the formation of one new C–S and two C–N bonds. The operationally simple protocol provides direct access to the highly functionalized 4-thioarylpyrroles with free-NH in good to excellent yields. The synthetic application of resulting 4-thioarylpyrroles was demonstrated by oxidation of the sulfur atom to the corresponding sulfoxide and sulfone.
Keywords: metal-free synthesis; 1,4-enediones; 4-thioarylpyrroles; thiol-Michael reaction; C–S bond formation